HUBUNGAN JARAK KELAHIRAN DENGAN KEJADIAN STUNTING DI KOTA KUPANG TAHUN 2023 - Henukh, Dina Melanieka Sintikhe (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2024)
Stunting is still a serious chronic nutritional problem and affects the growth and development of children in Indonesia. The province with the highest stunting prevalence rate in Indonesia in 2022 is East Nusa Tenggara, namely 35.3%, Kupang City contributed a stunting prevalence rate of 19.2%. Stunting occurs due to various factors including prenatal and postnatal factors. The aim of this research is to determine the relationship between birth spacing and the incidence of stunting among toddlers in the Kupang City area. This research uses a case control research design. The population in this study were toddlers at the Sikumana Community Health Center, with a research sample of 80 respondents. The research was conducted in the working area of ​​the Sikumana Health Center, Kupang City in August – September 2023. The statistical test used was the chii square test with an α value of 0.05. The research results showed that in the group of toddlers who experienced stunting, there were 57.5% of respondents who had a birth interval of less than two years. In the control group, namely toddlers who did not experience stunting, there were 32.5% of respondents who had a birth interval of less than two years. The results of the Chi-Square test showed that Asymp Sig (2-tailed) was 0.025 < α (0.05). Conclusion: Based on the research results, it was found that there was a relationship between birth spacing and the incidence of stunting. Keywords: Birth Spacing, Stunting, Toddlers